Ethical points of view of biotechnology’s public perception - Correa Soares, Bernardo Elias (Acta Bioethica, 2003)
The practice of biotechnological social control demands ethical bases in order to rationalize the application of scientific principles and for allowing benefits to society. While the use of recombinant technology in pharmaceutical and medical products has great acceptance by society, as consequence of the evident improvement caused by the cure of diseases, the consumer hasn't a clear idea of the real value of genetic research to improve food quality. There is a great demand for more scientific information by the public with the purpose of mobilizing society toward clarifications in the future biotechnological thought.